Allergic contact dermatitis caused by 2-hydroxyethyl methacrylate and ethyl cyanoacrylate contained in cosmetic glues among hairdressers and beauticians who perform nail treatments and eyelash extension as well as hair extension applications: A systematic review - Symanzik, Cara; Weinert, Patricia; Babić, Željka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; Kezic, Sanja; Macan, Marija; Macan, Jelena; Strahwald, Julia; Turk, Rajka; van der Molen, Henk F.; et al. (Contact Dermatitis, 2022)
Current cosmetic regulations primarily focus on protecting consumers, not the professional user who is subjected to a partly different, and certainly more intense exposure to hazardous substances. Against this background, this systematic review aims to compile and appraise evidence regarding skin toxicity of 2-hydroxyethyl methacrylate (HEMA; CAS no. 212-782-2) and ethyl cyanoacrylate (ECA; CAS no. 7085-85-0) contained in cosmetic glues used among hairdressers and beauticians who perform nail treatments and eyelash extension as well as hair extension applications. This systematic review followed the Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) 2020 recommendations for reporting systematic reviews and meta-analysis. In total, six publications from six countries were eligible for this systematic review. A meta-analysis revealed that hairdressers and beauticians have a ninefold increased risk of developing contact allergy to HEMA compared with controls who are not hairdressers and beauticians. Results for ECA are lacking. The results of this systematic review clearly show that—regarding contact allergy to acrylates—it is not appropriate to apply risk assessment for consumers to hairdressers and beauticians who occupationally handle cosmetic glues. The regulations in existence do not adequately address occupational risks for hairdressers and beauticians connected with the use of acrylate-containing cosmetic substances and need reconsideration.
CRIS-Team Scopus Importer:2022-02-25
Keywords: 2-hydroxyethyl methacrylate; contact dermatitis; ECA; ethyl cyanoacrylate; glue; hairdresser; HEMA; occupational; occupational diseases; skin diseases

Association of hairdressing with cancer and reproductive diseases: A systematic review - Babic, Zeljka; Macan, Marija; Franic, Zrinka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; John, Swen M.; Symanzik, Cara; Uter, Wolfgang; Weinert, Patricia; Van Der Molen, Henk F.; Kezic, Sanja; et al. (Journal of Occupational Health, 2022)
Objectives To review recent epidemiological studies investigating carcinogenic or reprotoxic effects among hairdressers who seem to be at greater risk for systemic adverse effects of chemicals released from hair care products than consumers. Methods A systematic review according to the PRISMA-P guidelines was performed and included studies published from 2000 to August 2021, in which cancer or adverse reproductive effects were diagnosed in 1995 and onward. Data were synthetized qualitatively due to the small number of studies, heterogeneity of study designs, outcomes, and methods. Results Four studies investigating cancer frequencies and six studies investigating effects on reproduction among hairdressers were identified. All were of good quality and with low risk of bias. Only one of the four studies found an increased risk of cancer reporting nine times higher odds for bladder cancer in hairdressers than the population-based controls. Three other studies investigating bladder and lung cancer, and non-Hodgins lymphoma did not find an increased risk in hairdressers. Regarding reprotoxic effects, numerous outcomes were investigated including menstrual disorders, congenital malformations, fetal loss, small-for-gestational age newborns, preterm delivery, and infertility. Increased risk was found for ventricular septal defect in newborns of fathers working as hairdressers. Furthermore, several indices of poor neonatal or maternal health were significantly associated with mothers working as hairdresser. Conclusions Despite the scarce evidence that hairdressers are at increased risk of carcinogenic or reprotoxic effects related to their trade, such health risks cannot be ruled out. Therefore, preventive efforts to diminish occupational exposures to hairdressing chemicals should be targeted.
CRIS-Team WoS Importer:2022-09-02

Contact allergy to ingredients of hair cosmetics in female hairdressers and female consumers—An update based on IVDK data 2013–2020 - Uter, Wolfgang; Hallmann, Sarah; Gefeller, Olaf; Brans, Richard; Symanzik, Cara; Oppel, Eva; Lang, Claudia; Kränke, Birger; Treudler, Regina; Geier, Johannes (Contact Dermatitis, 2023)
Background: Hair cosmetic products contain several, partly potent contact allergens, including excipients like preservatives. Hand dermatitis in hairdressers is common, scalp and face dermatitis in clients or self-users (summarised here as ‘consumers’) may be severe. Objective: To compare frequencies of sensitization to hair cosmetic ingredients and other selected allergens between female patch tested patients working as hairdressers and consumers without professional background, respectively, who were tested for suspected allergic contact dermatitis to such products. Methods: Patch test and clinical data collected by the IVDK (https://www.ivdk.org) between 01/2013 and 12/2020 were descriptively analysed, focusing on age-adjusted sensitization prevalences in the two subgroups. Results: Amongst the 920 hairdressers (median age: 28 years, 84% hand dermatitis) and 2321 consumers (median age: 49 years, 71.8% head/face dermatitis), sensitization to p-phenylenediamine (age-standardised prevalence: 19.7% and 31.6%, respectively) and toluene-2,5-diamine (20 and 30.8%) were most common. Contact allergy to other oxidative hair dye ingredients was also more commonly diagnosed in consumers, whereas ammonium persulphate (14.4% vs. 2.3%) and glyceryl thioglycolate (3.9 vs. 1.2%) as well as most notably methylisothiazolinone (10.5% vs. 3.1%) were more frequent allergens in hairdressers. Conclusions: Hair dyes were the most frequent sensitizers both in hairdressers and in consumers; however, as indication for patch testing may differ, prevalences cannot directly be compared. The importance of hair dye allergy is evident, often with marked coupled reactivity. Workplace and product safety need to be further improved.
CRIS-Team Scopus Importer:2023-06-30
Keywords: clinical epidemiology; contact allergy; hair cosmetics; hairdressers; RRID:SCR_001905; surveillance

Differences between hairdressers and consumers in skin exposure to hair cosmetic products: A review - Symanzik, Cara; Johansen, Jeanne D.; Weinert, Patricia; Babić, Željka; Hallmann, Sarah; Havmose, Martin S.; Kezic, Sanja; Macan, Marija; Macan, Jelena; Strahwald, Julia; Turk, Rajka; van der Molen, Henk F.; et al. (Contact Dermatitis, 2022)
Hairdressers are at high risk of developing occupational hand eczema. Opinions on the health and safety concerns of nonfood consumer products, such as cosmetics and their ingredients, consider the exposure of a “common consumer,” which may not account for occupational exposure of hairdressers. As a result, there is a parlous scenario in which serious safety concerns about occupational exposures are present. The purpose of this review is to compare the frequency of exposure to various types of hair cosmetic products among hairdressers and consumers. Database searches for this review yielded a total of 229 articles; 7 publications were ultimately included. The analysis showed that—dependent on the task—hairdressers were exposed 4 to 78 times more than consumers to a wide spectrum of hair cosmetic products used in their daily working life, ranging from shampoos, conditioners, oxidative and nonoxidative hair colors, to bleaching agents. The highest frequency was found for coloring hair with oxidative hair color. Consumer use frequency does not appear to be appropriate for representing hairdresser exposure. The current standards do not effectively address the occupational risks associated with hairdressers' use of cosmetics. The findings of this study should cause current risk-assessment procedures to be reconsidered.
CRIS-Team Scopus Importer:2022-02-25
Keywords: contact dermatitis; exposure; hairdressers; occupational; occupational diseases; skin diseases

Genotoxicity of oxidative hair dye precursors: A systematic review - Babić, Željka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; John, Swen M.; Symanzik, Cara; Uter, Wolfgang; Weinert, Patricia; van der Molen, Henk F.; Kezic, Sanja; Macan, Jelena; Turk, Rajka (Human & Experimental Toxicology, 2023)
This systematic review, conducted according to the PRISMA guidelines, focuses on genotoxicity of oxidative hair dye precursors. The search for original papers published from 2000 to 2021 was performed in Medline, Web of Science, Cochrane registry, Scientific Committee on Consumer Safety of the European Commission and German MAK Commission opinions. Nine publications on genotoxicity of p-phenylenediamine (PPD) and toluene-2,5-diamine (p-toluylenediamine; PTD) were included, reporting results of 17 assays covering main genotoxicity endpoints. PPD and PTD were positive in bacterial mutation invitro assay, and PPD tested positive also for somatic cell mutations in the Rodent Pig-a assay invivo. Clastogenicity of PPD and PTD was revealed by invitro chromosomal aberration assay. The alkaline comet assay invitro showed DNA damage after PPD exposure, which was not confirmed invivo, where PTD exhibited positive results. PPD induced micronucleus formation invitro, and increased micronucleus frequencies in mice erythrocytes following high dose oral exposure invivo. Based on the results of a limited number of data from the classical genotoxicity assay battery, this systematic review indicates genotoxic potential of hair dye precursors PPD and PTD, which may present an important health concern for consumers and in particular for professional hairdressers.
CRIS-Team Scopus Importer:2023-03-24
Keywords: genotoxicity; Hair dyes; mutagenicity; p-phenylenediamine; p-toluylenediamine; toluene-2; 5-diamine

Occupational Exposure of Hairdressers to Airborne Hazardous Chemicals: A Scoping Review - Kezic, Sanja; Nunez, Roberto; Babic, Zeljka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; John, Swen M.; Macan, Marija; Symanzik, Cara; Uter, Wolfgang; Weinert, Patricia; Turk, Rajka; et al. (International Journal of Environmental Research and Public Health, 2022)
Introduction: Exposure to hazardous chemicals released during hairdressing activities from hair care products puts hairdressers at risk of adverse health effects. Safety assessments of hair products are mainly focused on consumers, but exposure for professional hairdressers might be substantially higher. Objective: To identify and assess available research data on inhalation exposures of professional hairdressers. Methods: A systematic search of studies between 1 January 2000 and 30 April 2021 was performed in Medline, Embase, Web of Science and in Cochrane registry, toxicological dossiers of the Scientific Committee on Consumer Safety (SCCS) of the European Commission as well as the German MAK Commission. Studies reporting quantitative data on airborne concentrations of chemicals in the hairdresser's workplace were considered. The outcome was an airborne concentration of chemicals in the working environment, which was compared, when possible, with current occupational exposure limits (OEL) or guidance levels. Results: In total, 23 studies performed in 14 countries were included. The average number of hairdressing salons per study was 22 (range 1-62). Chemicals most frequently measured were formaldehyde (n = 8), ammonia (n = 5), total volatile organic compounds (TVOC) (n = 5), and toluene (n = 4). More than fifty other chemicals were measured in one to three studies, including various aromatic and aliphatic organic solvents, hydrogen peroxide, persulfate, and particulate matter. Most studies reported environmental air concentrations, while personal exposure was measured only in seven studies. The measured air concentrations of formaldehyde, ammonia, and TVOC exceeded OEL or guidance values in some studies. There was large variability in measuring conditions and reported air concentrations differed strongly within and between studies. Conclusion: Hairdressers are exposed to a wide spectrum of hazardous chemicals, often simultaneously. Airborne concentrations of pollutants depend on salon characteristics such as ventilation and the number of customers but also on used products that are often country- or client-specific. For exposure to formaldehyde, ammonia, and TVOC exceeding OELs or guidance values for indoor air was observed. Therefore, occupational exposure should be taken into account by safety regulations for hair care products.
CRIS-Team WoS Importer:2022-04-22
Keywords: airborne exposure; indoor exposure; health effects; inhalation; hairdressers; hair salons

Prevalence and incidence of hand eczema in hairdressers—A systematic review and meta-analysis of the published literature from 2000–2021 - Havmose, Martin S.; Kezic, Sanja; Uter, Wolfgang; Symanzik, Cara; Hallmann, Sarah; Strahwald, Julia; Weinert, Patricia; Macan, Marija; Turk, Rajka; Van Der Molen, Henk F.; Babic, Zeljka; Macan, Jelena; et al. (Contact Dermatitis, 2022)
Background: Hairdressers are commonly affected by hand eczema (HE) due to skin hazardous exposure such as irritants and allergens in the work environment. Objective: To give an overview of the current prevalence, incidence, and severity, as well as the pattern of debut and the contribution of atopic dermatitis on HE in hairdressers. Methods: A systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines was performed. Studies published from 2000 to April 2021 that fulfilled predefined eligibility criteria were retrieved. Results: A pooled lifetime prevalence of 38.2% (95% confidence interval [CI] 32.6-43.8), a pooled 1-year prevalence of 20.3% (95% CI 18.0-22.6), and a pooled point prevalence of 7.7% (95% CI 5.8-9.6) of HE was observed in hairdressers. The lifetime prevalence in fully trained hairdressers and hairdressing apprentices was almost identical. The pooled incidence rate of HE was 51.8 cases/1000 person-years (95% CI 42.6-61.0) and the pooled prevalence of atopic dermatitis was 18.1% (95% CI 13.6-22.5). Conclusion: HE is common in hairdressers and most hairdressers have debut during apprenticeship. The prevalence of atopic dermatitis in hairdressers is comparable with estimates in the general population, indicating that occupational exposures are the main factor in the increased prevalence of HE in hairdressers. This warrants a strategic and collective effort to prevent HE in hairdressers.
CRIS-Team Scopus Importer:2022-02-11

Respiratory toxicity of persulphate salts and their adverse effects on airways in hairdressers: a systematic review - Macan, Jelena; Babic, Zeljka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; John, Swen M.; Macan, Marija; Symanzik, Cara; Uter, Wolfgang; Weinert, Patricia; Van Der Molen, Henk F.; Kezic, Sanja; et al. (International Archives of Occupational and Environmental Health, 2022)
Objective To review the literature on respiratory effects of persulfate salts (PS) or hair bleaches in hairdressers and animal models exploring mechanisms behind PS-induced asthma. Methods A systematic review according to the PRISMA guidelines was performed. Studies published from 2000 to July 2021 that fulfilled predefined eligibility criteria were retrieved. Data were not quantitatively synthesized due to the heterogeneity of study designs, outcomes and methods. Results Forty-two articles were included. PS are indicated as the main cause of occupational rhinitis and asthma in hairdressers, and one of the leading causes of occupational asthma in some European countries. Bleaching products are indicated as the most important factor for development of respiratory symptoms, lung function decline, and leaving the hairdressing profession. Risk estimates from a good quality prospective study showed up to 3.9 times higher risk for wheezing and breathlessness in hairdressers aged >= 40 years than in matched controls, and 20 times higher risk in hairdressers to develop respiratory symptoms from exposure to bleaching powder than controls. Pathophysiological mechanisms of the respiratory response to PS are not yet fully elucidated, but may include non-specific and specific immune responses. Conclusions Hairdressing is associated with a wide spectrum of respiratory adverse effects, of which bleaching products were indicated as the most hazardous. Preventive measures for reducing inhalatory exposure to PS in hair salons should be re-evaluated, including adopting occupational exposure limits at EU level, and encouraging use of safer bleach formulations. PROSPERO registration number CRD42021238118.
CRIS-Team WoS Importer:2022-04-08

Skin Toxicity of Selected Hair Cosmetic Ingredients: A Review Focusing on Hairdressers - Symanzik, Cara; Weinert, Patricia; Babic, Zeljka; Hallmann, Sarah; Havmose, Martin Stibius; Johansen, Jeanne Duus; Kezic, Sanja; Macan, Marija; Macan, Jelena; Strahwald, Julia; Turk, Rajka; Van Der Molen, Henk F.; et al. (International Journal of Environmental Research and Public Health, 2022)
The safety assessment of cosmetics considers the exposure of a ‘common consumer’, not the occupational exposure of hairdressers. This review aims to compile and appraise evidence regarding the skin toxicity of cysteamine hydrochloride (cysteamine HCl; CAS no. 156-57-0), polyvi-nylpyrrolidone (PVP; CAS no. 9003-39-8), PVP copolymers (CAS no. 28211-18-9), sodium laureth sulfate (SLES; CAS no. 9004-82-4), cocamide diethanolamine (cocamide DEA; CAS no. 68603-42-9), and cocamidopropyl betaine (CAPB; CAS no. 61789-40-0). A total of 298 articles were identified, of which 70 were included. Meta-analysis revealed that hairdressers have a 1.7-fold increased risk of developing a contact allergy to CAPB compared to controls who are not hairdressers. Hairdressers might have a higher risk of acquiring quantum sensitization against cysteamine HCl compared to a consumer because of their job responsibilities. Regarding cocamide DEA, the irritant potential of this surfactant should not be overlooked. Original articles for PVP, PVP copolymers, and SLES are lacking. This systematic review indicates that the current standards do not effectively address the occupational risks associated with hairdressers’ usage of hair cosmetics. The considerable irritant and/or allergenic potential of substances used in hair cosmetics should prompt a reassessment of current risk assessment practices.
CRIS-Team Scopus Importer:2022-07-22
Keywords: cocamide diethanolamine; cocamidopropyl betaine; cosmet-ics; cysteamine hydrochloride; hairdresser; hairdressing; hand eczema; polyvinylpyrrolidone; polyvinylpyrrolidone copoly-mers; sodium laureth sulfate

Systematic review on skin adverse effects of important hazardous hair cosmetic ingredients with a focus on hairdressers - Uter, Wolfgang; Strahwald, Julia; Hallmann, Sarah; Johansen, Jeanne D.; Havmose, Martin S.; Kezic, Sanja; Van Der Molen, Henk F.; Macan, Jelena; Babic, Zeljka; Franic, Zrinka; Macan, Marija; Turk, Rajka; et al. (Contact Dermatitis, 2022)
Background The burden of occupational hand eczema in hairdressers is high, and (partly strong) allergens abound in the hair cosmetic products they use. Objectives To systematically review published evidence concerning contact allergy to an indicative list of active ingredients of hair cosmetics, namely, p-phenylenediamine (PPD), toluene-2,5-diamine (PTD), persulfates, mostly ammonium persulfate (APS), glyceryl thioglycolate (GMTG), and ammonium thioglycolate (ATG), concerning the prevalence of sensitization, particularly in terms of a comparison (relative risk; RR) between hairdressers and non-hairdressers. Methods Following a PROSPERO-registered and published protocol, eligible literature published from 2000 to February 2021 was identified, yielding 322 publications, and extracted in standardized publication record forms, also considering risk of bias. Results Based on 141 publications, the contact allergy prevalence to PPD was 4.3% (95% CI: 3.8-4.9%) in consecutively patch tested patients. Other ingredients were mostly tested in an aimed fashion, yielding variable, and partly high contact allergy prevalences. Where possible, the RR was calculated, yielding an average increased sensitization risk in hairdressers of between 5.4 (PPD) and 3.4 (ATG). Additional evidence related to immediate-type hypersensitivity, experimental results, exposures, and information from case reports was qualitatively synthesized. Conclusions An excess risk of contact allergy is clearly evident from the pooled published evidence from the last 20 years. This should prompt an improvement in working conditions and product safety.
CRIS-Team WoS Importer:2022-11-11